Behavioral Response of Arctocephalus australis to Pedestrian Disturbance During the Breeding Season: Implications for Wildlife Tourism Management - Maite Arangüena‐Proaño; Carlos Calvo‐Mac; Yann Tremblay (Marine Mammal Science, 2026)
The South American fur seal ( Arctocephalus australis ) breeds in dense colonies along the Peruvian coast, mostly within protected areas managed by the Servicio Nacional de Áreas Naturales Protegidas por el Estado (SERNANP). To support responsible wildlife tourism near breeding sites, we evaluated the behavioral responses to controlled pedestrian approaches at Punta Coles, within the Reserva Nacional Sistema de Islas, Islotes y Puntas Guaneras (RNSIIPG). Specifically, we (a) quantified A. australis responses to pedestrian disturbance and (b) identified the factors influencing variation in individual alert distance (i.e., the distance at which animals first detect and respond to human presence) during the breeding season. We conducted 61 standardized approaches across five colonies, recording synchronized video, GPS tracks, and sound‐level measurements, and obtained wind conditions from satellite‐derived data. Linear models with stepwise Akaike Information Criterion (AIC) selection identified the key predictors of alert distance. Alert distance increased with colony size, and was greater when wind conditions favored human scent transport toward the colony (i.e., smaller wind‐track angle difference). These results underscore the importance of sensory cues and colony‐size effects in shaping human–pinniped interactions, consistent with antipredator and vigilance theory. The empirical relationship derived here provides a practical, transferable framework for establishing evidence‐based buffer distances to guide sustainable pinniped tourism.